Creep and shrinkage of high-strength self-compacting concrete: experimental and analytical analysis - Aslani, F (2013)
In the present paper, a numerical and experimental study about creep and shrinkage behavior of a high strength self-compacting concrete is performed. Two new creep and shrinkage prediction models based on the comprehensive analysis on the available models of both conventional concrete and self-compacting concrete are proposed for high strength self-compacting concrete structures. In order to evaluate the predictability of the proposed models, an experimental program was carried out. A concrete which develops 60 MPa within 24 h was used to obtain experimental results. Several specimens were loaded: (i) at different ages and (ii) with different stress-to-strength ratios. Deformation in non-loaded specimens was also measured to assess shrinkage. All specimens were kept under constant stress during at least 600 days in a climatic chamber with temperature and relative humidity of 20 degrees C and 50%, respectively. Results showed that the new models were able to predict deformations with good accuracy, although provided deformations overestimated slightly.